LEGAL AND ETHICAL ISSUES OF BUSINESS COMMUNICATION - Ayvazyan, Naira (Foreign Languages for Special Purposes, 2024)
The purpose of this article is to explore and analyze the legal and ethical issues of business communication that all large companies face in the complex global business environment of the 21st century.In today's technology-rich era, businesses are required to have an elaborate code of conduct and ethics that should be followed as a tool by every member of the organization.Along with business communication skills, there is also the legal aspect to consider. In international law, the legal aspects of business communication are problematic. Therefore, international companies in some countries rely on legal advice to ensure that they comply with all legal norms of communication. Some areas of business communications are strictly regulated by law, while others can lead to potential civil litigation.It is important to note that understanding the potential legal and ethical issues and implications of communication in business is important for both entrepreneurs and managers, as well as all employees.
Keywords: business communication; ethical behavior; legal issues; concept of ethics; breach of privacy; business policy; legal aspect